Acceptability, feasibility, and factors affecting implementation of a gender-sensitivity training for HIV providers and staff in Uganda: a mixed methods, quasi-experimental controlled pilot trial - K M. Sileo; R K. Wanyenze; A Anecho; R L. Luttinen; K Weston; B Mukasa; S C. Mukama; S H. Vermund; S L. Dworkin; J F. Dovidio; B S. Taylor; T S. Kershaw (BMC Public Health)
Abstract Background Health workers play a critical role in providing gender-sensitive HIV care. However, without adequate training, they may inadvertently reinforce negative gender norms that hinder engagement in care. To improve ART services in sub-Saharan Africa, effective implementation strategies, including trainings, are essential. Methods This study evaluated the feasibility and acceptability of a novel 4-session, gender-sensitivity training for HIV health and lay workers in rural and peri-urban Uganda. We conducted a pilot quasi-experimental controlled trial in 2022–23, utilizing data from three sources: process data from 144 providers and 238 clients, qualitative post-intervention focus groups and interviews with 53 training attendees, and stakeholder interviews with 12 community leaders and facilitators. We employed thematic analysis guided by the Consolidated Framework for Implementation Research (CFIR). Results The training was highly rated by attendees via brief post-session surveys, with 99% of sessions deemed satisfactory. Qualitative feedback indicated that the sessions were perceived as appropriate for addressing providers’ gaps in delivering gender-sensitive care and as beneficial for participants. High feasibility was evidenced by 100% of intervention steps delivered (fidelity checklists), 86% attendance (attendance logs), and 98.6% and 94.8% recruitment of eligible providers and clients (study records), respectively. Through qualitative exit focus groups, factors that positively affected acceptability and feasibility included tactics to gain support from supervisors, the use of experienced facilitators and active learning approaches, and the consideration of the health system context in delivery (e.g., cadre mix, location). Suggested improvements encompassed addressing interpersonal and structural barriers to client-centered care, incorporating community sensitization, streamlining content, and enhancing mentorship follow-ups. Stakeholders recognized the training’s alignment with national health priorities and emphasized the need for clarity regarding its integration with existing training curricula and ongoing stakeholder engagement. Conclusions This study underscores the acceptability and feasibility of a gender-sensitivity training program for HIV providers; further evaluation of the program is warranted. Identified factors influencing implementation can inform enhancements to gender-focused training initiatives to improve the quality of HIV services and enhance client engagement and health outcomes. Trial registration Clinicaltrials.gov, NCT05178979, registered: November 15, 2021.